P50 Experiences of delivering in-situ simulations in the emergency department at night. (3rd November 2019) - Edwards, Sarah; Harris, Sam; Roland, Damian
Abstract : Background: In-situ simulation is well established in medical education, being used from everything from assessment to human factors training. 1 In emergency medicine, in-situ simulation has been used for many years to try and practice skills and understand human factors in teams better. 1 With ever increasing patient numbers presenting through the doors of emergency departments, training and learning has become a challenge. 2 This work will look at the experiences of doing in-situ simulations with the staff on night shifts. Summary of work: We already have established in-situ simulation training weekly within our department. There are ad-hoc simulations around this as well. The whole team from nursing and medical students, through to senior doctors and nurses get involved. What we have started doing, is running simulations at night times to test the systems in place within the emergency department at night. We describe the first two of our simulations that occurred and the challenges of trying to enable them to happen along with strategies to overcome this. Scenario 1 was a trauma that presented at 6 am in the morning. Scenario 2 was a hanging in the emergency department toilets at 4 am. Summary of results and discussion: Approximately, 15 people were involved between both simulations. Their feedback was collated. The overall feedback was positive. This was seen as a good learning opportunity; it was nice to be learning at night time and 'I never knew we had a toilet there'. Negatives included people being unsure of the purpose of the simulation. The department learned that at night time it was unclear who was to respond to the emergency bells. It is clear there is an appetite for this type of learning. This is only the initial work and further night time simulations will need to be evaluated. Recommendations: Strategies to enable simulations to happen overnight include senior nurses allocating staff to become available for the simulations, aim for a specific time in the night for it to happen, thus allowing staff to be freed up. Junior doctors will also be allocated for the simulation. It is clear in our early work this can be a valuable learning opportunity even on a night shift. References: Petrosoniak A, Auerbach M, Wong AH, Hicks CM. In situ simulation in emergency medicine: Moving beyond the simulation lab. Emerg Med Australas . 2017 Feb;29(1):83–88. doi: 10.1111/1742-6723.12705 Ahn J, Golden A, Bryant A, Babcock C. Impact of a Dedicated Emergency Medicine Teaching Resident Rotation at a Large Urban Academic Center. West J Emerg Med . 2016;17(2):143–148. doi:10.5811/westjem.2015.12.28977